If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1) * b = 0 Solving -1b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '-1'. b = 0 Simplifying b = 0
| 3.5x-1=0.5(7x+2) | | f(x)81x^2-100=0 | | x=1x^2+13x+40 | | 6(3a-b)-6(5b-7a)= | | (x)=1x^2+5x-50 | | X+.071=3 | | f(x)=1x^2+5x-50 | | x=1x^2-9x+14 | | 5(k+1)=16 | | f(x)=1x^2-9x+14 | | x+.07=3 | | 0.6666667y+6=y | | 3t+8(2t-6)=16-4(v+7) | | 11x-9y=14 | | f(x)=5cosx | | 2(1.5m+3)=8.5m-1 | | 6p+11q+4= | | (13b-5)-3(4b+1)=-4 | | -3(6p+4)-2(4-14p)=3(9+3p) | | 80=4w+5 | | 2x+8=6x+2 | | m+11.3=-7.2 | | -66-5x+x^2=0 | | 2m-4m=6 | | x+31=14 | | 8x-15x-30x-51x=53x+31x-72 | | 6x+15y=2000000 | | Y=12-2(0) | | 6x=9+8 | | 8x-2x-2=1 | | 3(c+7)-6c=4 | | 4cos(2x-60)=2 |